2019
DOI: 10.1371/journal.pone.0214736
|View full text |Cite
|
Sign up to set email alerts
|

Actin-binding domains mediate the distinct distribution of two Dictyostelium Talins through different affinities to specific subsets of actin filaments during directed cell migration

Abstract: Although the distinct distribution of certain molecules along the anterior or posterior edge is essential for directed cell migration, the mechanisms to maintain asymmetric protein localization have not yet been fully elucidated. Here, we studied a mechanism for the distinct localizations of two Dictyostelium talin homologues, talin A and talin B, both of which play important roles in cell migration and adhesion. Using GFP fusion, we found that talin B, as well as its C-terminal actin-bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…The third term is a representation of the adhesion energy between the membrane and the cortex. Proteins connecting the membrane to the cortex have been found around the boundary of migrating cells [ 18 , 47 ]. Their contribution to adhesion energy is commonly modeled using linear elastic spring with spring constant κ [ 17 , 18 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…The third term is a representation of the adhesion energy between the membrane and the cortex. Proteins connecting the membrane to the cortex have been found around the boundary of migrating cells [ 18 , 47 ]. Their contribution to adhesion energy is commonly modeled using linear elastic spring with spring constant κ [ 17 , 18 , 23 , 24 ].…”
Section: Methodsmentioning
confidence: 99%
“…In Dictyostelium , TalA is implicated in cell-substrate adhesion and cytokinesis in the unicellular vegetative state, while TalB is involved in cell motility, force transmission, and development during the transition to a multicellular state ( Niewohner et al, 1997 ; Tsujioka et al, 2004 ; Tsujioka et al, 2008 ). Furthermore, both molecules have also been shown to bind to actin and possess conserved FERM and I/LWEQ domains similar to their Metazoan counterparts ( Tsujioka et al, 2008 ; Tsujioka et al, 2019 ). Intriguingly, double knockouts of talA and talB in Dictyostelium demonstrated a severe defect in cell-substrate adhesion and migration ( Tsujioka et al, 2008 ), suggesting a critical role for both TalA and TalB in both cellular processes.…”
Section: Cell-substrate Adhesions In Organisms Evolutionarily Distant...mentioning
confidence: 99%
“…More recently it was shown that talin A binds actin filaments pre-stretched by myosin II especially at the uropod of developed cells, while talin B is enriched at the anterior cell pole excluded from those regions [195].…”
Section: Talb0mentioning
confidence: 99%